Can Cities be Net-Positive? A Systematic Literature Review - El Kehal, Mohammed Ihabe (2024)
Cities depict the evolution of human civilization, manifesting both triumphs and tribulations, and playing a crucial role in shaping the trajectory of our future. Is this future going to be a socially and ecologically just one? Or is it going to be a harbinger for an unjust dystopian nightmare? On the backdrop of these philosophical speculations, rose a question that intrigues the need for an answer: “Can Cities be Net-Positive?”. In a bid to find answers, the paper takes an inductive interpretative qualitative path, bolstered by the Gioia Method. A total of 57 articles were analyzed, and a Gioia data structure was constructed. The findings suggest that cities can be net-positive, and there are existing concepts that may support achieving this goal. Some of these concepts are regenerative design, biomimicry, biodiversity-inclusive design, and biophilic urbanism. The paper also draws attention to the established theory of Positive Development (PD) as a valid path to achieve net-positive outcomes. An example of an emerging net-positive urban form was highlighted which is the Positive Energy District (PED). However, a radical change in paradigms is necessary to achieve this seemingly unrealistic goal. This paper claims that human-nature integration could be the bottom-line for this new radical paradigm shift. It also highlights the social and ecological duality meaning that urban actions should always consider these two vectors. And that moving from ‘doing less bad’ to ‘doing more good’ is not enough, instead, our actions should draw absolute ‘net-positive’ outcomes. The paper concludes with exploring some of the research implications, highlighting its limitations, and suggesting future directions for further inquiry.